Painful ulcerations: the sole clinical sign of mixed cryoglobulinaemia secondary to marginal zone lymphoma. Issue 4 (7th April 2022) - Gan, Christian; Howard, Matthew David; Mulcahy, Anthea; Yazdabadi, Anousha
Abstract : A man in his 70s with background vascular disease presented with 7 months of painful non-resolving lower leg ulcers with eschar and petechiae, left lower ear lobe ulceration and dusky inflammation of the right ear. He demonstrated good bilateral pedal pulses and no peripheral oedema. No lymphadenopathy was palpated. Biopsy suggested leucocytoclastic vasculitis on chronic stasis changes. Blood investigations showed elevated rheumatoid factor and mixed polyclonal IgG and monoclonal IgM cryoglobulins. He was diagnosed with mixed cryoglobulinaemia, and consequent conducted flow cytometry revealed CD5 +marginal zone lymphoma with elevated serum free light chains and kappa/lambda ratio. One-month following rituximab and chlorambucil therapy, the patient's pain had much improved, ear ulcers had healed and several leg ulcers had reduced in width and depth. The petechial eruption had also resolved.